Mobile application to support maintenance of wireless sensor networks = Aplikacja mobilna wspierająca zadanie utrzymania bezprzewodowej sieci sensorów - Piotrowski, Krzysztof; Koropiecki, Igor; Zielony, Przemysław; Powroźnik, Piotr; Szulim, Robert (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
This work describes the progress towards creating a tool realized as an application for mobile devices to maintain sensor nodes installed in the monitored environment using Bluetooth Low Energy. The application is generic, so it supports any set of monitored data and maintenance functions, as long as the node application includes the basic functionality required for the maintenance task.
Keywords: komputeryzacja; przyrządy pomiarowe; informatyka; technologie informacyjne